The Rights and Role of Indigenous Women in Climate Change Regime - Prior, Tahnee Lisa; Heinämäki, Leena (Arctic Review on Law and Politics, 2017)
The Rights and Role of Indigenous Women in The Climate Change Regime Climate change has direct and indirect consequences for individuals and their human rights (McInerney-Lankford et al. 2011). With the Arctic warming at twice the global rate, its inhabitants already experience many of these challenges. Marginalized groups, like women and indigenous peoples, are particularly vulnerable, with existing research providing evidence of ongoing and potential threats to their roles in community adaptation and in shaping change (Cameron 2011, Arctic Resilience Report 2016). While women’s rights are formally codified as human rights under the Convention on the Elimination of Discrimination against Women (CEDAW), and indigenous peoples’ human rights are codified and recognized in the UN Declaration on the Rights of Indigenous Peoples (UNDRIP), indigenous women’s rights are often neglected at both the international and local level. In this article, we apply an intersectional lens to demonstrate that indigenous and non-indigenous women are agents of change. In doing so, we examine how a human rights based approach might ensure indigenous women’s participatory role and legal status in the international climate change regime, as well as its related programs.